A Multi-Criteria Decision-Making Approach for Teaching Quality Evaluation in University Music Programs Using Plithogenic Sets and Weighted Decision Models - Mingjiao Liu; Hongdan Wan (Neutrosophic Sets and Systems)
Chinese colleges and universities have been studying and implementing quality monitoring systems for music art instruction as a key teaching management project. How to fairly and impartially evaluate the teaching skills of professors of art and music is a crucial problem in college and university administration. Evaluation of university music program have various criteria affecting the decision-making process. So, we used the multi-criteria decision-making methodology (MCDM) to deal with these criteria and select best program. We used the Plithogenic sets with the MCDM methodology to deal with uncertainty information. We used the operators of Plithogenic to combine the Plithogenic numbers. We use the weighted product model (WPM) to rank the alternatives. The weights of criteria are computed using the normalized crips values. The results show the Musical Performance Proficiency of Teachers criterion has the highest rate and Engagement with Music Industry and Professional Development criterion has the lowest rate. We compare the proposed methodology with other MCDM methods. The results show the proposed methodology is effective.